Ultrastructural and clinical evidence of subretinal debris accumulation in type 2 macular telangiectasia. Issue 11 (13th September 2012) - Cherepanoff, Svetlana; Killingsworth, Murray C; Zhu, Meidong; Nolan, Timothy; Hunyor, Alex P; Young, Stephanie H; Hageman, Gregory S; Gillies, Mark C
Abstract : Aims: To describe subretinal debris found on ultrastructural examination in an eye with macular telangiectasia (MacTel) type 2 and on optical coherence tomography (OCT) in a subset of patients with MacTel type 2. Methods: Blocks from the mid-periphery and temporal perifovea of an eye with clinically documented MacTel type 2 were examined with electron microscopy (EM). Cases came from the Sydney centre of the MacTel project and the practices of the authors. Results: On EM examination, subretinal debris was found in the perifovea with accumulation of degenerate photoreceptor elements in the subretinal space. Despite the substantial subretinal debris, there was minimal retinal pigment epithelial (RPE) reaction. Focal defects were seen in the inner limiting membrane in the perifovea. Of the 65 Sydney MacTel project participants, three (5%) had prominent yellow material at the fovea. OCT revealed smooth mounds between the RPE and the ellipsoid region. The material was hyperautofluorescent. Conclusions: This study suggests that subretinal accumulation of photoreceptor debris may be a feature of MacTel type 2. Ultrastructural and OCT evidence of disease beyond the vasculature, involving photoreceptors and Muller cells, is presented.